Evaluation of Oxalic Acid treatments against the Mite Varroa destructor and Secondary Effects on Honey Bees Apis mellifera - Noureddine Adjlane; El-Ounass Tarek; Nizar Haddad (Tehran University of Medical Sciences, 2016)
Background: The Varroa destructor varroasis is a very serious parasite of honeybee Apis mellifera. The objective of this study was to evaluate the effectiveness of Varroa treatment using organic acid (oxalic acid) in Algeria identifying its side effects on bee colonies. Methods: Treatment was conducted in one apiary consisting 30 colonies kept in Langstroth hives kind. Oxalic acid dripped directly on bees 5ml of this solution of oxalic acid per lane occupied by a syringe. Three doses were tested: 4.2, 3.2 and 2.1% oxalic acid is 100, 75 and 50 g of oxalic acid dehydrate in one litter of sugar syrup (1water to1 surge) concentration. Results: The percentage of average efficiency obtained for the first dose was 81%, 72.19% for the second dose, and 65% for third one, while the dose of 100 g oxalic acid causes a weakening of honey bee colonies. Conclusion: The experiments revealed that clear variation in the treatment efficiency among colonies that this might be related to brood presence therefore in order to assure the treatment efficiency oxalic acid should be part of a bigger strategy of Varroa treatment.